Optimasi Lampu Lalu Lintas Simpang Tabuik Kota Pariaman Menggunakan Graf Fuzzy Berbasis FIS Tipe Mamdani - Cahyani, Alda Wahyu Regita; Rosha, Media (Journal of Mathematics UNP, 2023)
Poor traffic light regulation is one of the causes of congestion. One of the factors contributing to congestion is inadequate traffic light control, especially at the Tabuik Kota Pariaman intersection. Fuzzy graph is a part of mathematical science that combines graph theory with fuzzy logic. Fuzzy graphs can be used as a method to solve congestion problems related to traffic light durations. This research aims to determine the duration of green light based on queue length. The data collected includes primary data on traffic duration, road width, and the number of vehicles passing through each leg of the intersection. The research results show that by using a fuzzy graph based on the Mamdani fuzzy inference system, the overall average at the Tabuik intersection, the total duration of green light obtained is 80 seconds, which is a decrease of 8.75% from the initial condition, while the total duration of red light obtained is 404 seconds, which is an increase of 1.76% from the initial condition.